(untitled) - Bly, Robert W. (Franklin Lakes, NJ., 1998)
Here is the most complete and up-to-date resource of model business correspondence for every conceivable occasion. From sample letters, memos and e-mails, this guide allows the user to use samples as is, or adapt for their own purpose. This book contains more than 300 model documents demonstrating the key elements necessary to convey the writer's message. Easy organization allows user to quickly identify the specific letter needed.
Keywords: Commercial correspondence.,Memorandums,Facsimile transmission